1979
DOI: 10.1111/j.1532-5415.1979.tb01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Parameters in the Elderly: An Argument Against New Geriatric Normal Values*

Abstract: Erythrocyte parameters in 292 unselected geriatric patients were studied retrospectively. Statistically significant mean decreases compared to the laboratories' normal mean values were found in the red blood cell count (RBC), hemoglobin level, hematocrit, and mean corpuscular hemoglobin concentration; there also was a slight increase in mean corpuscular volume and mean corpuscular hemoglobin. However, when 17 patients with a hemoglobin level less than 10 gm/dl or a hematocrit reading less than 35 percent were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

1982
1982
1994
1994

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 9 publications
2
12
0
1
Order By: Relevance
“…The BM cytology, includ ing EM/ratio and differential count, were within the normal range for adults (table II), showing similar figures to those previously reported in aged persons (12,21,23]. Low hemoglobin values in old age have been pre viously reported [9,11]. Iron deficiency is common in healthy elderly people [10,14], and since the BM hemosiderin content in the BM was found to be low, it clearly points to iron deficiency as the main cause of the mild anemia observed in our group.…”
Section: Discussionsupporting
confidence: 77%
“…The BM cytology, includ ing EM/ratio and differential count, were within the normal range for adults (table II), showing similar figures to those previously reported in aged persons (12,21,23]. Low hemoglobin values in old age have been pre viously reported [9,11]. Iron deficiency is common in healthy elderly people [10,14], and since the BM hemosiderin content in the BM was found to be low, it clearly points to iron deficiency as the main cause of the mild anemia observed in our group.…”
Section: Discussionsupporting
confidence: 77%
“…This suggests that falling haemoglobin levels may be a normal physiological response to aging, the so called 'anaemia of senescence'. In contrast, other studies have demonstrated a high incidence of anaemia in elderly indi viduals, associated with treatable causes (Htoo et al 1979;Milne & Williamson 1972).…”
Section: Normal Haemoglobin Levels In Elderly Patientsmentioning
confidence: 84%
“…Many hematologic studies have indicated that there is a normal decline in the RBC count and Hb level with age. Nevertheless, a few investigators have concluded that there is no change in these measurements in the absence of some pathologic process 16,17 . This difference seems to be mainly due to a bias in selection of the subjects studied.…”
Section: Discussionmentioning
confidence: 97%
“…Although several modifications of the original Metz method have been developed, 16,17 they are still too complicated for clinical use. We modified Wickramasinghe's method by applying a multiple automatic cell harvester.…”
Section: Discussionmentioning
confidence: 99%